Medical error and adverse events in oncologic diagnosis: report of two clinical cases - Portocarrero Ramos, Carlos Alberto (2022)
Errors in medical practice, associated with inappropriate communication, praxis and other factors have been reported in several studies and it is necessary to analyze them due to the consequences for the patient, the family, the health professional and the institutions; even more so if the final diagnosis is oncologic. The aim of the present article is to report two clinical cases in which misdiagnosis occurs. A review of various clinical documents has been carried out, after authorization of the two patients and a semi-structured interview. Factors that may lead to possible errors during the oncologic diagnostic process and affect the doctor-patient relationship are discussed, such as deficits in the communication process, educational and academic deficits, consultation time and deontological aspects.